Zinc-loaded nano-zeolite crystallite catalyst as well as preparation method and application thereof

By using zinc-supported nanozeolite crystal catalyst, the problems of low activity of existing catalysts in closed-loop recovery of polylactic acid and difficult to separate products are solved, and efficient depolymerization and recovery of PLA is achieved, and the catalyst has good cycle stability.

CN119793520APending Publication Date: 2025-04-11FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958624.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing catalysts have low activity and difficult separation of products in closed-loop recovery of polylactic acid, resulting in low recycling efficiency of PLA and waste of resources.

Method used

A zinc-supported nanozeolite crystal catalyst consisting of nanozeolite crystals and ZnOx supported on its surface is used to achieve uniform dispersion and high activity of ZnOx through a specific preparation method.

Benefits of technology

The depolymerization efficiency and closed-loop selectivity of polylactic acid are improved, and the efficient recovery of PLA is achieved. The catalyst is easy to separate from the product and has high cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793520A_ABST
    Figure CN119793520A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-loaded nano zeolite crystallite catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The zinc-loaded nano zeolite crystallite catalyst provided by the invention comprises nano zeolite crystallite and ZnOx loaded on the surface of the nano zeolite crystallite. The nano zeolite crystallite provided by the invention has ultra-small particle size, high external specific surface area and rich hydroxyl sites, is beneficial to increasing the accessibility of a high-molecular polymer and a catalyst, and promotes highly uniform dispersion, anchoring and electronic regulation and control of ZnOx active sites. The zinc-loaded nano-zeolite crystallite catalyst can realize uniform dispersion of ZnOx under high loading capacity, and the particle size of the zinc-loaded nano-zeolite crystallite catalyst is obviously reduced on the nano level; and the heterogeneous loaded catalyst is easy to realize effective separation of a recovered product and the catalyst. During application, PLA can be efficiently, quickly, simply and easily depolymerized and recycled with low energy consumption without being pretreated, and the catalytic depolymerization activity is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a zinc-loaded nano-zeolite crystal catalyst and a preparation method and application thereof. Background Art

[0002] The white pollution generated by discarded plastics has caused great harm to the ecological environment and human health. In recent years, with the continuous enhancement of people's environmental awareness, bio-based degradable polymers have received increasing attention and have been greatly developed.

[0003] Polylactic acid (PLA) is considered to be one of the best candidate materials to replace traditional petroleum-based plastics due to its advantages such as suitable strength, biodegradability and wide source of raw materials. It occupies an important position in the biodegradable bio-based plastics market. However, the application of PLA has the following problems: First, the degradation rate of PLA in the natural environment is very slow. The accumulation of a large number of discarded PLA plastic products will inevitably cause environmental pollution. PLA plastic products that enter the marine ecosystem may even last for hundreds of years. Second, CO 2 As a product of complete degradation of PLA, it causes serious waste of carbon resources; thirdly, the raw materials for synthesizing PLA mainly come from sugary foods, and large-scale de novo production will pose a threat to global food security. The high demand for energy, economy and raw material consumption makes the production of PLA face greater challenges. Therefore, converting PLA into usable chemicals for recycling can well deal with the problems existing in the application of PLA.

[0004] Chemical recovery of monomers is an industrially feasible method for PLA recovery. In this process, the polymer is converted into lactide (LD) monomer and used for polymer reproduction, which can effectively avoid the introduction of impurities and alleviate the pressure of raw material production. In existing research, the scheme for closed-loop recovery of PLA to LD monomer widely uses stannous octoate or alkali metal / transition metal oxides and inorganic salts as catalysts. With the diversification of recovery schemes, existing catalysts face problems such as low activity and difficult product separation. Therefore, it is urgent to provide a highly active heterogeneous catalyst to improve the closed-loop recovery and utilization capacity of polylactic acid. Summary of the invention

[0005] The purpose of the present invention is to provide a zinc-loaded nano-zeolite crystal catalyst and a preparation method and application thereof. The zinc-loaded nano-zeolite crystal catalyst provided by the present invention has high activity and can have high catalytic depolymerization efficiency and ring closure selectivity in the process of polymer depolymerization and selective ring closure.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x .

[0008] Preferably, the nano zeolite crystallites are ZSM-5 nano zeolite crystallites.

[0009] Preferably, the ZnO x The particle size is ≤4nm.

[0010] Preferably, the ZnO x The mass percentage of Zn(II) in the zinc-loaded nano-zeolite crystal catalyst is 0.5-50%.

[0011] The present invention also provides a method for preparing the zinc-supported nano-zeolite crystal catalyst described in the above technical solution, comprising the following steps:

[0012] (1) mixing a silicon source, an aluminum source, tetrapropylammonium hydroxide and water, and sequentially performing aging, hydrothermal treatment and dialysis purification to obtain a nano-zeolite crystallite dispersion;

[0013] (2) Mixing the nano-zeolite crystal dispersion obtained in step (1) with a water-soluble zinc salt, and sequentially drying and calcining to obtain a zinc-loaded nano-zeolite crystal catalyst.

[0014] Preferably, in step (1), the molar ratio of the silicon source, the aluminum source, tetrapropylammonium hydroxide and water is 1:(0.00125-0.00685):0.2:6.96.

[0015] Preferably, the aging in step (1) is carried out at room temperature, and the aging time is 12 to 48 hours.

[0016] Preferably, the hydrothermal treatment in step (1) comprises low-temperature hydrothermal treatment and high-temperature hydrothermal treatment performed sequentially; the temperature of the low-temperature hydrothermal treatment is 80-100°C, and the time of the low-temperature hydrothermal treatment is 50-130 minutes; the temperature of the high-temperature hydrothermal treatment is 130-150°C, and the time of the high-temperature hydrothermal treatment is 80-140 minutes.

[0017] Preferably, the calcination in step (2) includes low-temperature calcination and high-temperature calcination performed sequentially; the temperature of the low-temperature calcination is 150-200°C, and the time of the low-temperature calcination is 1.5-3 hours; the temperature of the high-temperature calcination is 350-550°C, and the time of the high-temperature calcination is 4-8 hours.

[0018] The present invention also provides the use of the zinc-loaded nano zeolite crystal catalyst described in the above technical solution or the zinc-loaded nano zeolite crystal obtained by the preparation method described in the above technical solution as a catalyst in the closed-loop recovery of polylactic acid into lactide monomer.

[0019] The invention provides a zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x The nano-zeolite crystals provided by the present invention have ultra-small particle size, high external specific surface area, and abundant hydroxyl sites, which are beneficial to increase the accessibility of high molecular polymers and catalysts and promote ZnO x Highly uniform dispersion, anchoring and electronic regulation of active sites; zinc-loaded nanozeolite crystal catalysts can achieve ZnO at high loadings x The uniform dispersion of ZnO and the significant reduction of its particle size at the nanometer level, and the heterogeneous supported catalyst can easily achieve the effective separation of the recovered product and the catalyst; the highly dispersed ZnO x As the active site center, it is beneficial to activate the carbonyl group of macromolecular PLA and realize the selective ring closure to generate lactide (LD) monomer, so that PLA can be depolymerized and recycled efficiently, quickly, simply and with low energy consumption without pre-treatment, and the catalytic depolymerization activity is high; ZnO has a strong interaction with the zeolite crystal framework x It provides abundant and enhanced Lewis acid sites, and has high catalytic depolymerization efficiency and ring closure selectivity in the polymer depolymerization and selective ring closure process. The results of the examples show that the external specific surface area of ​​the zinc-loaded nano-zeolite crystals provided by the present invention is 167-495 m 2 / g, and it was used as a catalyst for the depolymerization and selective ring closure of PLA. PLA could achieve more than 80% depolymerization within 3 hours under simple conditions, and the LD monomer recovery yield could reach 58%, which showed high activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD patterns of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6 of the present invention, ZnOnano prepared in Comparative Example 1, SC prepared in Comparative Example 6, and commercial zinc oxide;

[0021] Figure 2 TEM images of zinc-supported nano-zeolite crystal catalysts prepared in Examples 2 to 4 and 6 of the present invention;

[0022] Figure 3 UV-vis graphs of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6 of the present invention, ZnOnano prepared in Comparative Example 1, SC prepared in Comparative Example 6, and commercial zinc oxide;

[0023] Figure 4XPS graphs of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6 of the present invention and ZnOnano prepared in Comparative Example 1;

[0024] Figure 5 XRD diagrams of the catalysts prepared in Comparative Examples 2 to 5 of the present invention;

[0025] Figure 6 UV-vis graphs of the catalysts prepared in Comparative Examples 2 to 5 of the present invention;

[0026] Figure 7 This is a comparison chart of the polylactic acid depolymerization rate and the lactide monomer recovery yield of application examples 1 to 6 of the present invention;

[0027] Figure 8 This is a result diagram of the application of SC prepared in comparative application example 1 of the present invention to the depolymerization and ring-closing reaction of polylactic acid;

[0028] Fig. 9 TEM images of commercial bulk zinc oxide in comparative application example 2 of the present invention and ZnOnano catalyst prepared in comparative application example 3;

[0029] Fig.10 This is a comparison chart of the depolymerization rates of polylactic acid depolymerization closed-loop recycling in Application Example 4 and Comparative Application Examples 2, 3, and 6;

[0030] Fig.11 A comparison chart of the cycle stability of polylactic acid depolymerization closed-loop recovery in Application Example 4 of the present invention and Comparative Application Example 6;

[0031] Fig.12 This is a thermogravimetric analysis comparison diagram of Application Example 4 of the present invention and Comparative Application Example 6 before and after the catalyst recycling application for depolymerization closed-loop recovery of polylactic acid. DETAILED DESCRIPTION

[0032] The invention provides a zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x .

[0033] The zinc-loaded nano-zeolite crystal catalyst provided by the present invention includes nano-zeolite crystals. In the present invention, the nano-zeolite crystals are preferably ZSM-5 nano-zeolite crystals, and the particle size of the ZSM-5 nano-zeolite crystals is preferably 6 to 20 nm, more preferably 8 to 15 nm. The nano-zeolite crystals in the zinc-loaded nano-zeolite crystal catalyst provided by the present invention have a high external specific surface area within the above-mentioned particle size range, and the zeolite crystals are rich in hydroxyl defects, which is beneficial to ZnO x The dispersion and anchoring of active sites make the catalyst less likely to be deactivated due to the loss of active sites, and the cyclic catalytic stability is high.

[0034] The zinc-loaded nano-zeolite crystal catalyst provided by the present invention also includes ZnO loaded on the surface of the nano-zeolite crystal. x In the present invention, the ZnO x As a structurally different zinc species, this non-stoichiometric zinc oxide species has unique electronic structure and catalytic properties.

[0035] In the present invention, the ZnO x The particle size is preferably ≤4nm. Nano-zeolite crystals have ultra-small particle size, high external specific surface area, and abundant hydroxyl sites. The ZnO x The particle size within the above range is beneficial to increase the accessibility of the polymer and the catalyst and promote the ZnO x Highly uniform dispersion, anchoring and electronic regulation of active sites.

[0036] In the present invention, the ZnO x The mass percentage of Zn(II) in the zinc-supported nano-zeolite crystal catalyst is preferably 0.5-50%, more preferably 3.8-35.7%, and further preferably 13.4%. The present invention controls the loading amount of Zn(II) within the above range, which can make the catalyst have excellent catalytic activity.

[0037] The present invention also provides a method for preparing the zinc-supported nano-zeolite crystal catalyst described in the above technical solution, comprising the following steps:

[0038] (1) mixing a silicon source, an aluminum source, tetrapropylammonium hydroxide and water, and sequentially performing aging, hydrothermal treatment and dialysis purification to obtain a nano-zeolite crystallite dispersion;

[0039] (2) Mixing the nano-zeolite crystal dispersion obtained in step (1) with a water-soluble zinc salt, and sequentially drying and calcining to obtain a zinc-loaded nano-zeolite crystal catalyst.

[0040] The invention mixes a silicon source, an aluminum source, tetrapropylammonium hydroxide and water, and sequentially performs aging, hydrothermal treatment and dialysis purification to obtain a nano zeolite crystal dispersion.

[0041] In the present invention, the silicon source is preferably tetraethyl orthosilicate, silica sol, white carbon black or sodium silicate, and more preferably tetraethyl orthosilicate.

[0042] In the present invention, the aluminum source is preferably aluminum isopropoxide, aluminum chloride or aluminum sulfate, more preferably aluminum isopropoxide.

[0043] In the present invention, the tetrapropylammonium hydroxide is used as a template for synthesizing nano zeolite crystals.

[0044] In the present invention, the molar ratio of the silicon source, aluminum source, tetrapropylammonium hydroxide and water is preferably 1: (0.00125-0.00685): 0.2: 6.96, and more preferably 1: 0.005: 0.2: 6.96. The present invention controls the amount of each component within the above range, so that each raw material can fully react to form nano zeolite crystals.

[0045] In the present invention, the method of mixing the silicon source, aluminum source, tetrapropylammonium hydroxide and water preferably comprises: dissolving the silicon source and the aluminum source to obtain a mixed solution; and mixing the tetrapropylammonium hydroxide aqueous solution with the mixed solution.

[0046] In the present invention, the dissolution time of the silicon source and the aluminum source is preferably 3 to 12 hours, more preferably 6 to 10 hours. The present invention can fully dissolve the silicon source and the aluminum source within the above time.

[0047] The present invention has no particular limitation on the method for mixing the tetrapropylammonium hydroxide aqueous solution with the mixed solution, as long as the two can be mixed uniformly.

[0048] In the present invention, the aging is preferably carried out at room temperature; the aging time is preferably 12 to 48 hours, more preferably 24 to 30 hours. The present invention can hydrolyze tetraethyl orthosilicate and mix it evenly with other raw materials through aging.

[0049] In the present invention, the hydrothermal treatment preferably includes low-temperature hydrothermal treatment and high-temperature hydrothermal treatment performed sequentially.

[0050] In the present invention, the temperature of the low-temperature hydrothermal treatment is preferably 80-100°C, more preferably 90-100°C; the time of the low-temperature hydrothermal treatment is preferably 50-130min, more preferably 90-120min; the temperature of the high-temperature hydrothermal treatment is preferably 130-150°C, more preferably 140-150°C; the time of the high-temperature hydrothermal treatment is preferably 80-140min, more preferably 100-120min. The present invention facilitates the nucleation and growth of molecular sieve crystals from a mixed solution of a silicon source and a tetrapropylammonium hydroxide solution by sequentially performing low-temperature hydrothermal treatment and high-temperature hydrothermal treatment to obtain nano zeolite crystals. In an embodiment of the present invention, the hydrothermal treatment device is a microwave reactor.

[0051] In the present invention, the method of dialysis purification is preferably: placing the system after hydrothermal treatment in a dialysis bag, and placing the dialysis bag in an aqueous solution of tetrapropylammonium hydroxide for dialysis. In the present invention, the aqueous solution of tetrapropylammonium hydroxide is preferably a Watsons distilled water solution containing tetrapropylammonium hydroxide, and the concentration of the aqueous solution of tetrapropylammonium hydroxide is preferably 2-16mmol / L, more preferably 6-10mmol / L; the dialysis bag is preferably a cellulose semipermeable membrane with a molecular weight cutoff of 2-10KD; the temperature of the dialysis is preferably room temperature; the present invention has no special limitation on the total time of the dialysis, and the Watsons distilled water is replaced every 8-12 hours, and the dialysis is performed until the liquid outside the dialysis bag is neutral.

[0052] After obtaining the nano zeolite crystallite dispersion, the present invention mixes the nano zeolite crystallite dispersion with a water-soluble zinc salt, and sequentially performs drying and calcination to obtain a zinc-loaded nano zeolite crystallite catalyst.

[0053] In the present invention, the nano-zeolite crystallite dispersion is preferably concentrated or diluted to a concentration of 10 to 45 mg / g, preferably 25 to 30 mg / g, and then mixed with the water-soluble zinc salt.

[0054] In the present invention, the water-soluble zinc salt preferably includes one or more of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate, and more preferably zinc acetate. The present invention uses the above water-soluble zinc salt to provide zinc ions.

[0055] In the present invention, the amount of the water-soluble zinc salt added is preferably such that the mass percentage of Zn(II) in the zinc-supported nano-zeolite crystal catalyst is 0.5-50%, more preferably 3.8-35.7%, and further preferably 13.4%.

[0056] The present invention has no particular limitation on the method of mixing the nano-zeolite crystallite dispersion and the water-soluble zinc salt, as long as the water-soluble zinc salt can be completely dissolved in the nano-zeolite crystallite dispersion.

[0057] In the present invention, the drying method is preferably freeze drying, and the freeze drying temperature is preferably -38 to -48°C, more preferably -40 to -44°C. The present invention has no special limitation on the freeze drying time, and the solid can be dried to constant weight. In an embodiment of the present invention, the freeze drying time can be 72 to 144 hours. The present invention can maintain a smaller particle size of the nano zeolite crystallite and the water-soluble zinc salt mixture through freeze drying to prevent agglomeration caused by excessively high drying temperature.

[0058] In the present invention, the calcination preferably includes low-temperature calcination and high-temperature calcination performed sequentially.

[0059] In the present invention, the temperature of the low-temperature calcination is preferably 150-200°C, more preferably 200°C; the time of the low-temperature calcination is preferably 1.5-3h, more preferably 2h; the temperature of the high-temperature calcination is preferably 350-550°C, more preferably 350-400°C; the time of the high-temperature calcination is preferably 4-8h, more preferably 6h. The present invention can promote the removal of water in the molecular sieve crystals by low-temperature calcination, and remove the template by high-temperature calcination.

[0060] In the present invention, the calcination atmosphere is preferably air. The calcination in air can make zinc ions form zinc oxide species on the surface of nano zeolite crystallites.

[0061] The present invention also provides the use of the zinc-loaded nano-zeolite crystallites described in the above technical solution as a catalyst in the closed-loop recovery of polylactic acid into lactide monomer.

[0062] In the present invention, the polymer recovered from the closed-loop polylactic acid preferably includes a molecular weight of M w ~80000,M w ~110000 and one or more of polylactic acid plastic straw products.

[0063] In the present invention, the method of using the zinc-loaded nano zeolite crystals as a catalyst in the closed-loop recovery of polylactic acid into lactide monomer preferably comprises: dissolving the polymer in an organic solvent to obtain a polymer solution; mixing the polymer solution with the zinc-loaded nano zeolite crystal catalyst, and then performing a depolymerization and ring-closing reaction in a microwave reactor.

[0064] In the present invention, it is preferred that the polymer is dissolved in an organic solvent to obtain a polymer solution.

[0065] In the present invention, the ratio of the mass of the polylactic acid to the volume of the organic solvent is preferably 0.01 to 0.1 g / mL, more preferably 0.025 to 0.05 g / mL, and further preferably 0.036 g / mL.

[0066] In the present invention, the organic solvent is preferably N,N-dimethylformamide (DMF).

[0067] The present invention has no particular limitation on the method for dissolving the polymer in an organic solvent, as long as the polymer can be completely dissolved to form a polymer solution. In the present invention, the method for dissolving the polymer in an organic solvent is preferably carried out under heating, and the heating temperature is preferably 80 to 140° C., more preferably 90 to 120° C.; the heating time is preferably 5 to 20 minutes, more preferably 10 to 20 minutes.

[0068] After obtaining the polymer solution, the present invention preferably mixes the polymer solution with a zinc-supported nano-zeolite crystal catalyst, and then performs a depolymerization and ring-closing reaction in a microwave reactor.

[0069] In the present invention, the mass ratio of Zn(II) in the zinc-supported nano-zeolite crystal catalyst to the polymer in the polymer solution is preferably (0.001-0.02):1, more preferably 0.008:1.

[0070] The present invention has no particular limitation on the mixing method, as long as the polymer solution and the zinc-supported nano-zeolite crystal catalyst can be uniformly mixed. In an embodiment of the present invention, the mixing method can be stirring.

[0071] In the present invention, the temperature of the depolymerization ring-closing reaction is preferably 120-200°C, more preferably 140-180°C; the heating rate from room temperature to the depolymerization ring-closing reaction temperature is preferably 15-40°C / min, more preferably 20°C / min; starting from the time when the room temperature is raised to the temperature of the polylactic acid depolymerization ring-closing reaction, the time of the polylactic acid depolymerization ring-closing reaction is preferably 0.17-5h, more preferably 0.5-3h; the polylactic acid depolymerization ring-closing reaction is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring speed, as long as the polylactic acid depolymerization ring-closing reaction can proceed smoothly.

[0072] The present invention preferably cools the obtained reaction solution after the depolymerization ring-closing reaction. The present invention has no particular limitation on the cooling method, and any cooling method known in the art can be used. In an embodiment of the present invention, the cooling method can be natural cooling.

[0073] The zinc-loaded nano-zeolite crystals provided by the present invention have high external specific surface area and abundant hydroxyl sites, which is beneficial to ZnO x The active sites are dispersed, anchored and electronically regulated, and heterogeneous supported catalysts can easily achieve effective separation of recovered products and catalysts. Highly dispersed ZnO x As the active site center, it is beneficial to activate the carbonyl group of macromolecular PLA and realize the selective ring closure to generate lactide (LD) monomer, so that PLA can be depolymerized and recycled efficiently, quickly, simply and with low energy consumption without pre-treatment, and has high catalytic depolymerization activity. x , it has high catalytic depolymerization efficiency and ring closure selectivity in the process of polymer depolymerization and selective ring closure.

[0074] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0075] Example 1

[0076] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 35.7%, external specific surface area is 167m 2 / g;

[0077] The preparation method of the zinc-supported nano-zeolite crystal catalyst is as follows:

[0078] (1) Tetraethyl orthosilicate and aluminum isopropoxide are stirred and mixed at room temperature for 8 hours, and then tetrapropylammonium hydroxide aqueous solution is added, and aged at room temperature for 24 hours. After the aging, the mixed system is placed in a hydrothermal synthesizer, and low-temperature hydrothermal treatment is performed at 90°C for 90 minutes, and then high-temperature hydrothermal treatment is performed at 140°C for 100 minutes; the obtained dispersion is placed in a cellulose semipermeable membrane, and immersed in Watsons distilled water containing tetrapropylammonium hydroxide (the concentration of tetrapropylammonium hydroxide is 6 mmol / L) for dialyzing, and dialyzed at room temperature for 24 hours, and then Watsons distilled water is replaced several times until the aqueous solution is neutral, to obtain a nano zeolite crystal dispersion; the molar ratio of the silicon source, the aluminum source, the tetrapropylammonium hydroxide and the water is 1:0.005:0.2:6.96;

[0079] (2) The nano-zeolite crystal dispersion obtained in step (1) was adjusted to a solid content of 25 mg / g, and then Zn(CH 3 COO 2 ·2H 2 O (the mass percentage of Zn(Ⅱ) in the zinc-loaded nano-zeolite crystal catalyst, referred to as the loading amount of 35.7%) was mixed evenly, placed in a freeze dryer, and dried to constant weight at -48°C. In an air atmosphere, the temperature was raised to 200°C at 1°C / min, and maintained at 200°C for 2h to fully remove the water in the zeolite crystals, and then the temperature was further raised from 200°C to 350°C at 1°C / min, calcined at 350°C for 6h, and then cooled to room temperature to obtain a zinc-loaded nano-zeolite crystal catalyst (denoted as ZnO x / SC-35.7).

[0080] Example 2

[0081] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 30.1%, external specific surface area is 196m 2 / g;

[0082] The method for preparing the zinc-supported nano-zeolite crystal catalyst is different from that in Example 1 in that Zn(CH 3 COO 2 ·2H 2 The amount of O added was such that the loading amount of the zinc-supported nano-zeolite crystal catalyst was 30.1%. The remaining steps were the same as those in Example 1. The obtained zinc-supported nano-zeolite crystal catalyst was recorded as ZnO x / SC-30.1.

[0083] Example 3

[0084] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 22.9%, external specific surface area is 380m 2 / g;

[0085] The method for preparing the zinc-supported nano-zeolite crystal catalyst is different from that in Example 1 in that Zn(CH 3 COO 2 ·2H 2 The amount of O added was such that the loading amount of the zinc-supported nano-zeolite crystal catalyst was 22.9%. The remaining steps were the same as those in Example 1. The obtained zinc-supported nano-zeolite crystal catalyst was recorded as ZnO x / SC-22.9.

[0086] Example 4

[0087] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 13.4%, external specific surface area is 393m 2 / g;

[0088] The method for preparing the zinc-supported nano-zeolite crystal catalyst is different from that in Example 1 in that Zn(CH 3 COO 2 ·2H 2 The amount of O added was such that the loading amount of the zinc-supported nano-zeolite crystal catalyst was 13.4%. The remaining steps were the same as those in Example 1. The obtained zinc-supported nano-zeolite crystal catalyst was recorded as ZnO x / SC-13.4.

[0089] Example 5

[0090] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 7.3% and external specific surface area is 446m 2 / g;

[0091] The method for preparing the zinc-supported nano-zeolite crystal catalyst is different from that in Example 1 in that Zn(CH 3 COO 2 ·2H 2 The amount of O added was such that the loading amount of the zinc-supported nano-zeolite crystal catalyst was 7.3%. The remaining steps were the same as those in Example 1. The obtained zinc-supported nano-zeolite crystal catalyst was recorded as ZnO x / SC-7.3.

[0092] Example 6

[0093] A zinc-loaded nano-zeolite crystal catalyst, comprising nano-zeolite crystals and ZnO loaded on the surface of the nano-zeolite crystals. x Composition: Zn(Ⅱ) loading is 3.8%, external specific surface area is 495m 2 / g;

[0094] The method for preparing the zinc-supported nano-zeolite crystal catalyst is different from that in Example 1 in that Zn(CH 3 COO 2 ·2H 2 O was added in an amount such that the loading amount of the zinc-loaded nano-zeolite crystal catalyst was 3.8%. The remaining steps were the same as those in Example 1. The obtained zinc-loaded nano-zeolite crystal catalyst was recorded as ZnO x / SC-3.8.

[0095] Comparative Example 1

[0096] A method for preparing nano zinc oxide: Zn(CH 3 COO 2 ·2H 2 O was dissolved in water to obtain Zn(CH 3 COO 2 ·2H 2 O aqueous solution; the Zn(CH 3 COO 2 ·2H 2The O aqueous solution was placed in a freeze dryer and dried at -48°C to constant weight; in an air atmosphere, the temperature was increased to 200°C at 1°C / min and kept at 200°C for 2h, then the temperature was increased to 350°C at 1°C / min, and calcined at 350°C for 6h, and then cooled to room temperature to obtain nano zinc oxide (denoted as ZnOnano).

[0097] Comparative Example 2

[0098] A method for preparing zinc-loaded nano Z5 molecular sieve:

[0099] (1) Tetraethyl orthosilicate and aluminum isopropoxide were stirred and mixed at room temperature for 8 hours, and then tetrapropylammonium hydroxide aqueous solution was added and aged at room temperature for 24 hours; after the aging, the mixed system was placed in a hydrothermal synthesizer, and a low-temperature hydrothermal stage of 90°C was performed for 90 minutes, and then a high-temperature hydrothermal stage of 140°C was performed for 16 hours. The solution composition was a silicon source, an aluminum source, tetrapropylammonium hydroxide and water in a molar ratio of 1:0.01:0.2:6.96, and a nano H-ZSM-5 (denoted as Z5) molecular sieve solution was obtained.

[0100] (2) Place the nano Z5 molecular sieve solution in an oven at 80°C and dry for 16 h before measuring the solid content of the nano Z5 molecular sieve solution. Dilute the solid content to 25 mg / g and then add Zn(CH 3 COO 2 ·2H 2 O (Zn(Ⅱ) loading is 13.4%) and mixed evenly, placed in a freeze dryer, and dried to constant weight at -48°C. In an air atmosphere, a two-step calcination process was carried out successively, calcined at 200°C for 2h, further heated to 350°C, calcined at 350°C for 6h, and then cooled to room temperature to obtain zinc-loaded nano Z5 molecular sieve (denoted as ZnO x / Z5-13.4, the loading amount of Zn(Ⅱ) is 13.4%, and the external specific surface area is 141m 2 / g).

[0101] Comparative Example 3

[0102] The zinc-loaded nano Z5 molecular sieve was prepared according to the method of Comparative Example 2, which differs from Comparative Example 2 in that:

[0103] The loading amount of Zn(Ⅱ) was adjusted to 7.3%, and the obtained zinc-loaded nano Z5 molecular sieve was recorded as (ZnO x / Z5-7.3, the loading amount of Zn(II) is 7.3%).

[0104] Comparative Example 4

[0105] The zinc-loaded nano Z5 molecular sieve was prepared according to the method of Comparative Example 2, which differs from Comparative Example 2 in that:

[0106] The loading amount of Zn(Ⅱ) was adjusted to 3.8%, and the obtained zinc-loaded nano Z5 molecular sieve was recorded as (ZnO x / Z5-3.8, the loading amount of Zn(Ⅱ) is 3.8%).

[0107] Comparative Example 5

[0108] The zinc-loaded nano Z5 molecular sieve was prepared according to the method of Comparative Example 2, which differs from Comparative Example 2 in that:

[0109] The loading amount of Zn(Ⅱ) was adjusted to 2.0%, and the obtained zinc-loaded nano Z5 molecular sieve was recorded as (ZnO x / Z5-2.0, the loading amount of Zn(Ⅱ) is 2.0%).

[0110] Comparative Example 6

[0111] A nano zeolite crystal catalyst, the preparation method is:

[0112] (1) Tetraethyl orthosilicate and aluminum isopropoxide are stirred and mixed at room temperature for 8 hours, and then tetrapropylammonium hydroxide aqueous solution is added, and aged at room temperature for 24 hours. After the aging, the mixed system is placed in a hydrothermal synthesizer, and low-temperature hydrothermal treatment is performed at 90°C for 90 minutes, and then high-temperature hydrothermal treatment is performed at 140°C for 100 minutes; the obtained dispersion is placed in a cellulose semipermeable membrane, and immersed in Watsons distilled water containing tetrapropylammonium hydroxide (the concentration of tetrapropylammonium hydroxide is 6 mmol / L) for dialyzing, and dialyzed at room temperature for 24 hours, and then Watsons distilled water is replaced several times until the aqueous solution is neutral, to obtain a nano zeolite crystal dispersion; the molar ratio of the silicon source, the aluminum source, the tetrapropylammonium hydroxide and the water is 1:0.005:0.2:6.96;

[0113] (2) The nano-zeolite crystallite solution obtained in step (1) is placed in a freeze dryer and dried at -48°C to constant weight. In an air atmosphere, the temperature is raised to 200°C at 1°C / min and maintained at 200°C for 2h to fully remove water from the zeolite crystallite. The temperature is then further raised from 200°C to 350°C at 1°C / min, calcined at 350°C for 6h, and then cooled to room temperature to obtain nano-zeolite crystallite, which is recorded as SC.

[0114] Test Example 1

[0115] Figure 1 The XRD patterns of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6, the ZnOnano prepared in Comparative Example 1, the SC prepared in Comparative Example 6, and commercial zinc oxide are shown. Figure 1 It can be seen that the catalyst ZnO x / SC-35.7 and ZnOx / SC-30.1 have diffraction peaks at 2θ of 31.8°, 34.4°, and 36.3°, representing the diffraction peaks of ZnO(100), ZnO(002), and ZnO(101), respectively, indicating that the ZnO loaded on these two catalysts x It exists in a larger size on the zeolite crystals and cannot be effectively dispersed. x / SC-22.9 and the catalysts with further reduced loadings showed no diffraction peaks, indicating that the ZnO x A more even dispersion of species is beneficial for active site exposure.

[0116] Figure 2 The transmission electron microscope (TEM) images of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 2 to 4 and 6 are shown in FIG. Figure 2 It can be seen that the catalyst ZnO x / SC-22.9 did not form ZnO on the zeolite crystallites x The clusters of species further prove that ZnO x The uniform dispersion of ZnO x / SC-30.1 has obvious clusters, indicating that the ZnO x The dispersibility of the species decreases, and using MFI crystals as carriers can achieve active site dispersion at a high loading (not less than 22.9 wt%) to avoid cluster formation.

[0117] Figure 3 UV-visible diffuse reflectance (UV-vis) graphs of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6, ZnOnano prepared in Comparative Example 1, SC prepared in Comparative Example 6, and commercial bulk zinc oxide. Figure 3 It can be seen that in ZnO x / SC-22.9、ZnO x / SC-30.1、ZnO x The SC-35.7 catalyst exhibits characteristic ultraviolet absorption (370 nm) of normal crystalline zinc oxide, and the absorption intensity increases with the increase of loading, indicating that ZnO with a particle size of >4 nm (normal crystalline) x The catalyst ZnO x / SC-13.4 has no characteristic ultraviolet absorption at 370nm. This indicates that ZnO x / SC-13.4 can not only realize ZnO x It not only achieves highly uniform dispersion but also helps to form nanoparticles with further reduced particle size, thus promoting the contact between PLA macromolecules and active sites and the exposure of active sites.

[0118] Figure 4The X-ray photoelectron spectroscopy (XPS) of the zinc-supported nano-zeolite crystal catalysts prepared in Examples 1 to 6 and the ZnOnano prepared in Comparative Example 1 is shown in FIG. Figure 4 It can be seen that the Zn(2p 3 / 2 ) XPS spectrum is compared with that of ZnOnano. 2- The group has a stronger electronegativity, so ZnO x The characteristic peaks of the / SC-X catalyst shifted to higher binding energy values, indicating that the molecular sieve framework and ZnO x There is a strong interaction and plays a role in regulating the electron binding energy. In addition, with the increase of dispersion, Zn(2p 3 / 2 )The binding energy peak has an increasing trend, which is beneficial to the adsorption and activation of ester carbonyl groups in PLA.

[0119] Figure 5 The XRD patterns of the catalysts prepared in Comparative Examples 2 to 5 are shown below. Figure 5 It can be seen that the catalyst ZnO x / Z5-13.4 has shown diffraction peaks representing ZnO (100), ZnO (002), and ZnO (101), indicating that the loading amount (13.4%) can no longer be uniformly dispersed on the nano Z5 molecular sieve. The nano Z5 molecular sieve has a worse ZnO x Dispersed capabilities.

[0120] Figure 6 The UV-visible diffuse reflectance (UV-vis) graphs of the catalysts prepared in Comparative Examples 2 to 5 are shown in FIG. Figure 6 It is known that when nano Z5 molecular sieve is used as a carrier, the formation of large-sized ZnO nanoparticles can be effectively avoided only when the loading is lower than 3.8%.

[0121] Application Example 1

[0122] A method for using zinc-loaded nano-zeolite crystals as a catalyst in the closed-loop recovery of polylactic acid to lactide monomer: The depolymerization and closed-loop study of polylactic acid is carried out in a microwave reaction tube with a volume of 30 mL, and the reaction process is carried out in a closed system. First, 0.18 g of PLA spherical particles (particle size of 3 mm, Mw ~ 80,000) are added to the microwave reaction tube, followed by 5 mL of DMF. Rapidly heat to 100 ° C at a rate of 25 ° C / min, and heat at 100 ° C for 10 to 20 min to achieve uniform mixing of PLA and DMF, and take 0.1 mL of the homogeneous mixture and add it to 0.5 mL of deuterated chloroform (d-CDCl containing 1,3,5-trimethoxybenzene as an internal standard) 3 ) solution. Add 4.1 mg ZnO x / SC-35.7 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008) was then heated to 180°C at a rate of 20°C / min, and the depolymerization ring-closing reaction was carried out at this temperature. The heating was stopped at different time periods of the reaction, and the mixture was quickly cooled to room temperature. 0.1 mL of the homogeneous mixture was added to 0.5 mL of deuterated chloroform solution containing 1,3,5-trimethoxybenzene as an internal standard (d-CDCl 3 ), passed through a 0.22 μm organic microfilter, and transferred to a nuclear magnetic resonance tube for 1 H-NMR test was performed, and the depolymerization degree of PLA and the yield of lactide monomer were analyzed.

[0123]

[0124] pass 1 H-NMR test showed that the PLA methyl group (CH 3 ) proton region was integrated, 1,3,5-trimethoxybenzene was used as the internal standard, and the internal standard curve was used for quantitative analysis (based on the conversion of the lactic acid monomer repeating units contained in PLA) to calculate the polymer conversion rate. The PLA conversion rate calculation formula is shown in formula (1). 3 ) proton region was integrated, and the yield of LD was quantitatively analyzed using the internal standard curve. The yield calculation formula of LD is shown in formula (2). The result of the reaction for 3h was calculated, and the degree of depolymerization of polylactic acid was 46%, and the monomer yield was 28%.

[0125] Application Example 2

[0126] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is 4.8 mg ZnO x / SC-30.1 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 64%, and the monomer yield was 41%.

[0127] Application Example 3

[0128] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is 6.3 mg ZnO x / SC-22.9 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 80%, and the monomer yield was 49%.

[0129] Application Example 4

[0130] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is 10.8 mg ZnO x / SC-13.4 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 81%, and the monomer yield was 58%.

[0131] Application Example 5

[0132] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is 19.8 mg ZnO x / SC-7.3 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 74%, and the monomer yield was 49%.

[0133] Application Example 6

[0134] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is 19.8 mg ZnO x / SC-3.8 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 71%, and the monomer yield was 38%.

[0135] Test Example 2

[0136] Figure 7 is a comparison chart of polylactic acid depolymerization rate and lactide monomer recovery yield in application examples 1 to 6, Figure 7 It can be seen that in a series of zinc-loaded nano-zeolite crystal catalysts with different loadings prepared in the present invention, the loading amount is gradually reduced to achieve ZnO x The dispersion of active sites is beneficial to the depolymerization and selective closed-loop recovery of PLA, among which highly dispersed and small-sized ZnO x ZnO x / SC-13.4 catalyst has the highest catalytic depolymerization activity. When the loading is further reduced (7.3%, 3.8%), there will be no significant difference in dispersion and particle size, but more additional carriers need to be added, which is not conducive to the diffusion of macromolecular polymers and reduces depolymerization activity. Therefore, the ultra-small particle size and high specific surface area of ​​the crystalline MFI molecular sieve can achieve the dispersion of active sites under high loading, and achieve ZnO with the least amount of carrier added. x High dispersion and depolymerization recovery activity.

[0137] Comparative application example 1

[0138] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is the zeolite crystals SC prepared in Comparative Example 6 (the mass ratio of SC to PLA is 0.05, which is the same as the amount of carrier contained in Application Example 4). Under the same reaction conditions, the depolymerization and ring-closing process of PLA was not achieved, indicating that the unloaded zeolite crystal catalyst has no catalytic activity for the depolymerization and ring-closing reaction ( Figure 8 ), when different loading amounts of catalysts are used, the difference in the proportion of the carrier has no catalytic effect on the depolymerization process.

[0139] Comparative Application Example 2

[0140] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is a commercial zinc oxide catalyst (denoted as ZnO, with a particle size of >200 nm, and the TEM image of ZnO is as follows: Fig. 9 As shown in the figure, the mass ratio of Zn(II) to PLA in the catalyst is 0.008), and the result of reaction for 3h is calculated by the same calculation method, the degree of depolymerization of polylactic acid is 14%, and the monomer yield is 10%.

[0141] Comparative Application Example 3

[0142] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is ZnOnano catalyst (average particle size is 35 nm, TEM image of ZnOnano is as follows: Fig. 9 As shown in the figure, the mass ratio of Zn(II) to PLA in the catalyst is 0.008). The result of reaction time of 3h was obtained by the same calculation method, and the degree of depolymerization of polylactic acid was 69% and the monomer yield was 38%.

[0143] Comparative Application Example 4

[0144] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is ZnO x / Z5-13.4 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 68%, and the monomer yield was 35%.

[0145] It can be seen from comparative application examples 2 to 4 and application example 4 that the process of reducing the particle size of zinc oxide and improving the dispersibility is beneficial to increasing the exposure of active sites and promoting the depolymerization and ring closure of PLA.

[0146] Comparative Application Example 5

[0147] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is ZnO x / Z5-7.3 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 64%, and the monomer yield was 36%.

[0148] Comparative Application Example 6

[0149] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is ZnO x / Z5-3.8 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 64%, and the monomer yield was 42%.

[0150] Comparative Application Example 7

[0151] The depolymerization and ring-closing reaction of polylactic acid was carried out according to the method of Application Example 1. The difference from Application Example 1 is that the added catalyst is ZnO x / Z5-2.0 catalyst (the mass ratio of Zn(Ⅱ) to PLA in the catalyst is 0.008), and the result of reaction time of 3h was calculated by the same calculation method, the degree of depolymerization of polylactic acid was 59%, and the monomer yield was 31%.

[0152] Comparative Application Examples 4 to 6 further illustrate that the high dispersion and small size characteristics of active sites are important factors in controlling the efficient depolymerization of PLA. Comparative Application Examples 5 and 6 respectively obtain the best depolymerization effect in the catalysts with nano-zeolite crystallites and nano-zeolite (ZSM-5) as carriers, and further reduction of the loading is not conducive to depolymerization. At the same time, it is shown that under the high dispersion and small size characteristics of active sites, adding too much additional carrier due to low loading is not conducive to PLA depolymerization and ring closure, and the catalytic depolymerization activity is reduced. The ultra-small size of nano-zeolite crystallites, and the dispersion of active sites when used as carriers at higher loadings, have advantages in the depolymerization and ring closure process by reducing the diffusion limitation of the contact between macromolecular polymers and active sites while ensuring high exposure of active sites.

[0153] Test Example 3

[0154] Fig.10 The following is a comparison chart of the depolymerization rates of polylactic acid depolymerization closed-loop recycling in application example 4 and comparative application examples 2, 3, and 6. Fig.10It can be seen that the zinc-loaded nano zeolite crystals prepared by the present invention have high catalytic depolymerization activity in the closed-loop recovery process of polylactic acid depolymerization. Compared with the nano Z5 molecular sieve as a carrier, active site dispersion can be achieved at a higher loading and the addition of additional carriers can be reduced, which is beneficial to reduce the adverse effects on polymer diffusion, promote the rapid realization of PLA chemical recovery monomers and promote the actual recycling of plastic waste.

[0155] Fig.11 It is a comparison chart of the cyclic stability of Application Example 4 and Comparative Application Example 6 for depolymerization closed-loop recovery of polylactic acid. Fig.12 The thermogravimetric analysis comparison diagram of the catalyst used for polylactic acid depolymerization closed-loop recovery in Application Example 4 and Comparative Application Example 6 is shown in FIG. Fig.11 , 12 It can be seen that the zinc-supported nano-zeolite crystal catalyst is easy to separate from the product and is not prone to active site leaching, has a better ability to resist carbon deposition, and still has a higher depolymerization rate than the zinc-supported nano-Z5 molecular sieve catalyst after 4 cycles of use. After the secondary calcination to remove part of the carbon deposition, the depolymerization rate has a tendency to rise (5th), and the cycle stability is high. In addition, the ZnOnano catalyst can no longer cause depolymerization after the first depolymerization recovery application, which further shows that the carrier is important for improving the ZnO x Promoting the cyclic stability of active sites.

[0156] It can be seen from the above results that the zinc-loaded nano-zeolite crystals provided by the present invention have high catalytic depolymerization efficiency and ring closure selectivity in the polymer depolymerization and selective ring closure process. This is because the nano-zeolite crystals in the catalyst provided by the present invention have ultra-small particle size, high external specific surface area, and abundant hydroxyl sites, which are beneficial to increase the accessibility of the polymer and the catalyst and promote the ZnO x Highly uniform dispersion, anchoring and electronic regulation of active sites. Zinc-loaded nano-zeolite catalysts can achieve ZnO x The uniform dispersion of the catalyst and the significant reduction of its particle size at the nanometer level, and the heterogeneous supported catalyst can easily achieve the effective separation of the recovered product and the catalyst. x As an active site center, it is beneficial to activate the carbonyl group of macromolecular PLA and realize selective ring closure to generate LD monomer, so that depolymerization and recovery can be achieved efficiently, quickly, simply and with low energy consumption without the need for pre-treatment of PLA, and the catalytic depolymerization activity is high.

[0157] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A zinc-supported nano-zeolite crystal catalyst, characterized in that: The invention comprises a nano zeolite crystal and ZnO loaded on the surface of the nano zeolite crystal. x .

2. The zinc-supported nano-zeolite crystal catalyst according to claim 1, characterized in that: The nano zeolite crystallites are ZSM-5 nano zeolite crystallites.

3. The zinc-supported nano-zeolite crystal catalyst according to claim 1 or 2, characterized in that: The ZnO x The particle size is ≤4nm.

4. The zinc-supported nano-zeolite crystal catalyst according to claim 1, characterized in that: The ZnO x The mass percentage of Zn(II) in the zinc-loaded nano-zeolite crystal catalyst is 0.5-50%.

5. The method for preparing the zinc-supported nano-zeolite crystal catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a silicon source, an aluminum source, tetrapropylammonium hydroxide and water, and sequentially performing aging, hydrothermal treatment and dialysis purification to obtain a nano-zeolite crystallite dispersion; (2) Mixing the nano-zeolite crystal dispersion obtained in step (1) with a water-soluble zinc salt, and sequentially drying and calcining to obtain a zinc-loaded nano-zeolite crystal catalyst.

6. The preparation method according to claim 5, characterized in that: In the step (1), the molar ratio of the silicon source, the aluminum source, tetrapropylammonium hydroxide and water is 1:(0.00125-0.00685):0.2:6.

96.

7. The preparation method according to claim 5, characterized in that: The aging in step (1) is carried out at room temperature, and the aging time is 12 to 48 hours.

8. The preparation method according to claim 5, characterized in that: The hydrothermal treatment in step (1) includes low-temperature hydrothermal treatment and high-temperature hydrothermal treatment performed sequentially; the temperature of the low-temperature hydrothermal treatment is 80-100°C, and the time of the low-temperature hydrothermal treatment is 50-130 minutes; the temperature of the high-temperature hydrothermal treatment is 130-150°C, and the time of the high-temperature hydrothermal treatment is 80-140 minutes.

9. The preparation method according to claim 5, characterized in that: The calcination in step (2) includes low-temperature calcination and high-temperature calcination performed sequentially; the temperature of the low-temperature calcination is 150-200°C, and the time of the low-temperature calcination is 1.5-3 hours; the temperature of the high-temperature calcination is 350-550°C, and the time of the high-temperature calcination is 4-8 hours.

10. Use of the zinc-loaded nano zeolite crystal catalyst according to any one of claims 1 to 4 or the zinc-loaded nano zeolite crystal obtained by the preparation method according to any one of claims 5 to 9 as a catalyst in the closed-loop recovery of polylactic acid into lactide monomer.